In vitro and in vivo study of a nanoliposomal cisplatin as a radiosensitizer - Xiaomeng Zhang (Dove Medical Press, 2011)
Xiaomeng Zhang1*, Huanjun Yang1*, Ke Gu1, Jian Chen2, Mengjie Rui2, Guo-Liang Jiang11Departments of Radiation Oncology, Fudan University Shanghai Cancer Center; Department of Oncology, Shanghai Medical College,Fudan University,Shanghai, People’s Republic of China; 2School of Pharmacy, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; *Xiaomeng Zhang and Huanjun Yang share the first authorshipObjective: To investigate the in vitro and in vivo radiosensitization effect of an institutionally designed nanoliposome encapsulated cisplatin (NLE-CDDP).Materials and methods: NLE-CDDP was developed by our institute. In vitro radiosensitization of NLE-CDDP was evaluated by colony forming assay in A549 cells. In vivo radiosensitization was studied with tumor growth delay (TGD) in Lewis lung carcinoma. The radiosensitization for normal tissue was investigated by jejunal crypt survival. The radiosensitization studies were carried out with a 72 h interval between drug administration and irradiation. The mice were treated with 6 mg/kg of NLE-CDDP or CDDP followed by single doses of 2 Gy, 6 Gy, 16 Gy, and 28 Gy. Sensitization enhancement ratio (SER) was calculated by D0s of cell survival curves for A549 cells, doses needed to yield TGD of 20 days in Lewis lung carcinoma, or D0s of survival curves in crypt cells in radiation alone and radiation plus drug groups.Results: Our NLE-CDDP could inhibit A549 cells in vitro with half maximal inhibitory concentration of 1.12 µg/mL, and its toxicity was 2.35 times that observed in CDDP. For in vitro studies of A549 cells, SERs of NLE-CDDP and CDDP were 1.40 and 1.14, respectively, when combined with irradiation. For in vivo studies of Lewis lung carcinoma, the strongest radiosensitization was found in the 72 h interval between NLE-CDDP and irradiation. When given 72 h prior to irradiation, NLE-CDDP yielded higher radiosensitization than CDDP (SER of 4.92 vs 3.21) and slightly increased injury in jejunal crypt cells (SER of 1.15 vs 1.19). Therefore, NLE-CDDP resulted in a higher TGF than did CDDP (4.28 vs 2.70) when SERs were compared between experiments in vivo and in jejunal crypt cell studies.Conclusions: Our NLE-CDDP was demonstrated to have radiosensitization with TGF of 4.28 when administrated 72 h prior to irradiation.Keywords: cisplatin, liposome, nanoparticle, radiation, radiosensitization